Service Quality as the Key to Customer Satisfaction: An Empirical Analysis of BTPN Syariah Bank Siantar Timur - Sari, Wulan; Amelia, Ratih; Handayani, Cici; Amin Hou; Susanto (Journal of Business Integration Competitive, 2025)
This research seeks to assess the impact of employee service quality on customer satisfaction at BTPN Syariah Bank, East Siantar Branch. This research is both associative and quantitative. The study seeks to examine the correlation or impact of one variable on another. The study's demographic comprised 1,163 consumers of BTPN Syariah Bank, East Siantar Branch, in 2023. The sample for this study comprised 92 customers. This study employed simple regression analysis and hypothesis testing utilizing SPSS Version 25. This study's findings demonstrate that service quality positively and significantly impacts customer satisfaction at PTPN Syariah Bank, East Siantar Branch. Furthermore, customer satisfaction at BTPN Syariah Bank, East Siantar Branch, is primarily attributed to the independent variable of service quality, with the remaining 47.5% affected by other unexamined variables, including product quality and location.